Where's Waldo? : the ultimate travel collection - Handford, Martin (Cambridge, Mass. : Candlewick Press, 2008)
"The ultimate travel accessory! Five awe-inspiring Where's Waldo? books packed into one. Wherever you're going, however you're traveling--join the search for Waldo! First class!"-- Cover extension.
Keywords: Picture puzzles; Waldo (Fictitious character : Handford); Picture books